Seed quality and storage performance of wheat (Triticum aestivum.) and Soybean (Glycine max (L) Merrill) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agriculture Science in Plant Science (Seed Technology) at Massey University, Palmerston North, New Zealand - Singkanipa, Varenya (Massey University, 1996)
Five seedlots of wheat (Triticum spp.)cvs. Norseman. Otane, Karamu and two unknown cultivars. and four seedlots of soybean (Glycine max (L) Merrill)cv. Davis, two seedlots of cv. CH187 and one unknown cultivar were assessed for prestorage quality by using different laboratory methods ie purity, thousand seed weight, seed moisture content, germination, accelerated ageing, conductivity and seed health. The results of this study showed quality differences between seedlots of both wheat and soybean. Using seed germination and vigour data, three lots of wheat with high quality, two seedlots of soybean with high quality and one seedlot with low quality were chosen and adjusted to two different seed moisture contents (10% and 14% in wheat .and 8% and 12% in soybean). Seed samples of both species were stored in open storage (muslin bags) or sealed storage (aluminium foil packets) at 20°c 75%RH or 30°c 50% RH for 8 months. All wheat seedlots and two soybean seedlots were also stored under open storage at 30°c 95%RH. Seed quality was assessed at intervals of 1,2,4, 6 and 8 months. The seed moisture content of both species in open storagechanged to reach equilibrium moisture content (EMC) with the prevailing relative humidity. At 30°c 95%RH moisture content of wheat and soybean seeds increased up to 18.5-20.5% and 22-23%. respectively while at the same temperature but lower RH (50%), SMC fell to 8.2-8.5% and 5.2-5.5%, respectively. Both low and high initial SMC of seed stored at 20°c 75%RH either increased or decreased to reach an EMC of 12.8-13.6% for wheat and 9.8-10.1% for soybean. Under sealed storage at different storage temperatures and relative humidities SMC did not change from initial levels. At 20°c 75%SMC the type of storage container had no significant effect on germination percentage or conductivity in wheat and soybean after 8 months. At 30°c, however, the germination percentage of wheat and soybean with high initial SMC in sealed storage and in open storage high RH declined more rapidly during storage than the other treatments. Germination percentage correlated reasonably well with conductivity, with conductivity readings increasing as vigour decreased. At 30°c 95% both open and sealed storage at high initial SMC resulted in seed showing a conductivity value increase with longer storage time, indicating seedlot deterioration. All field fungi were eliminated from seed open stored at 30°c 95% but storage fungi developed rapidly in all seedlots after two months. The main genus involved was Aspergillus spp. but Penicillium spp. were also found at low levels in soybean. However, under 30°c 50%RH and 20°c 75%RH storage conduction field ftingi levels in wheat and soybean were reduced during storage and seed was either disinfected or remained infected at only low levels after 8 months storage. The main field fungus present in wheat was Fusarium spp.. In soybean both Fusarium spp. and Alternaria spp. survived well along with low levels of Colletotrichum spp.. The implications of pre-storage seed quality, seed moisture levels and storage environment and their effects on seed deterioration rate and extent are discussed. The role of field and storage fungi in affecting loss of seed viability in storage and the possibility of exploiting the storage environment to obtain pathogen free seed for planting is also considered.
Keywords: Wheat; Soybean; Seeds -- Quality; Seeds -- Viability